Gut microbiome and serum metabolome alterations in obesity and after weight-loss intervention - Liu, Ruixin; Hong, Jie; Xu, Xiaoqiang; Feng, Qiang; Zhang, Dongya; Gu, Yanyun; Shi, Juan; Zhao, Shaoqian; Liu, Wen; Wang, Xiaokai; Xia, Huihua; Liu, Zhipeng; et al. (Nature medicine, 2017)
Composition of gut bacteria and serum metabolites in young, obese individuals is partially restored following weight loss surgery, including Bacteroides thetaiotaomicron , which decreases serum glutamate levels and fat mass gain in mice. Emerging evidence has linked the gut microbiome to human obesity. We performed a metagenome-wide association study and serum metabolomics profiling in a cohort of lean and obese, young, Chinese individuals. We identified obesity-associated gut microbial species linked to changes in circulating metabolites. The abundance of Bacteroides thetaiotaomicron , a glutamate-fermenting commensal, was markedly decreased in obese individuals and was inversely correlated with serum glutamate concentration. Consistently, gavage with B. thetaiotaomicron reduced plasma glutamate concentration and alleviated diet-induced body-weight gain and adiposity in mice. Furthermore, weight-loss intervention by bariatric surgery partially reversed obesity-associated microbial and metabolic alterations in obese individuals, including the decreased abundance of B. thetaiotaomicron and the elevated serum glutamate concentration. Our findings identify previously unknown links between intestinal microbiota alterations, circulating amino acids and obesity, suggesting that it may be possible to intervene in obesity by targeting the gut microbiota.